DEVELOPMENT AND IMPLEMENTATION OF MODERN EDUCATION POLICY OF HIGHER EDUCATION INSTITUTION - Nikolay N. Mikhailov; Boris M. Vladimirskiy (Moscow Polytechnic University, 2016)
This article considers the main requirements to be taken into account when developing a university's education policy. The authors discuss conditions for the implementation of an innovative education policy and dwell on internal and external criteria for the evaluation of an education policy. The article substantiates the necessity of using different time scales when implementing a university education policy. Attention is drawn to the need for a gradual but significant overhaul of the curricula and syllabi, whereby only the universally useful knowledge and skills would remain. Three-level decision-making system to implement an education policy is introduced. Any university ought to combine in a holistic way all of its policies, such as education, research, financial, and planning ones. Therefore, their optimization should be carried out simultaneously.